Assessment Of Vehicle Emissions Associated With The Covid-19 Pandemic In Parts Of Greater Chennai Regime - Narayanan, RM; Laxmipriya, S; Rosario, C Benedict (Migration Letters, 2024)
Air pollution caused by vehicles has been described as the “disease of wealth”. Particulate matter PM2.5 and PM10, is a primary contaminant released by motorized vehicles. Since 2005, the number of motorised vehicles has increased by a factor of 24 and in recent years, private vehicles have accounted for over half of all daily trips taken by all individuals. In order to provide a clear understanding of emission sources and trends. Using real-time data on vehicle counts, types, fuel consumption, vehicle kilometers travelled (VKT), and ARAI emission factors, the study evaluated vehicle emissions associated to COVID-19 periods in ten locations across greater Chennai. The study also revealed that the modal share for vehicles ranged from 33% for two-wheeled vehicles to 25% for buses, 24% for three and four-wheeled vehicles and 18% for goods vehicles. The highest emission concentration of PM2.5 was observed in Koyambedu region with values of 0.000158 g/s-m2 and PM10 with the values of 0.000329 g/s-m2 followed by Ambattur and T. Nagar region.